An examination of the legal status, powers and roles of the Justices of the Peace in the Nigerian legal system - Akinloye, I. A. (Faculty of Law, University of the Free State, 2018)
It is not uncommon to hear of State governments in Nigeria appointing people as Justices of the Peace or of people adding ‘JP’ as a suffix to their names. Justices of the Peace are judicial officers appointed to conserve peace and perform quasi-judicial and administrative functions. They are appointed as officers of the courts and form part of the actors and drivers of the nation’s legal system. However, it appears that, over time, their relevance within the Nigerian context is fading away and that the office is gradually being reduced to political patronage. Consequently, this article seeks to raise awareness of the roles of Justices of the Peace in resolving minor disputes and fostering peaceful coexistence among citizens. It also highlights some of the challenges in the system with the aim of proffering a holistic reform. The article argues that the nature of the appointment and the poor capacity development of Justices of the Peace are the major banes of their effectiveness in Nigeria. Following the comparison of the Nigerian regime with the position in Jamaica, the article recommends how Justices of the Peace can be better equipped to be more effective within the context of the Nigerian legal system.
Keywords: Nigerian governments; Nigerian legal system; Justice; Peace; Law